Strategies of Controlling Iron Deficiency among Pregnant Women in the Peripheral Health Zones of Kinshasa, Democratic Republic of the Congo - Tamundele, Luhunu; Kasongo, Yumba; Mufeng, Mutinsumu; Mbokoso, Mwanamoki; Mbenza, Luvandu; Mugangu, Bashimbe; Nsutier, Oscar K.; Tshiama, Claudine; Bongo, Gédéon N. (BioScientific Review, 2023)
Anemia is the most widespread nutritional problem in the world. Its incidence rate is higher in South Asia and sub-Saharan Africa, where it affects a large proportion of women and children. The problem is accentuated where intestinal parasitic infection and malaria are common and this increases the morbidity and mortality rate. The current study attempted to evaluate the effectiveness of strategies involved in the control system of iron deficiency anemia in pregnant women. This study comprised of a quantitative, cross-sectional, and analytical design. Two reference health structures were chosen, namely Kimbanseke General Reference Hospital and Kinkole General Reference Hospital. The sample size consisted of 250 pregnant women. The data collection involved hemoglobin, thick drop, and stool analysis to assess the hematological and health status of surveyed pregnant women. Moreover, a questionnaire was used to collect socio-demographic data. The chi-square test was used to compare the variables and logistic regression was used to determine the effectiveness of applied strategies in order to control iron deficiency. Respondents were assured about the confidentiality of their responses and interviews were conducted in a secluded setting. The findings showed that the predominant age group was 20-24 years (34.0%), while most respondents were in the second semester of pregnancy (49.6%). Furthermore, most respondents had a secondary education (69.2%), their main activity was selling (47.2%), and most of them were married (84.0%). The level of hemoglobin was less than 11g/dl in most of the respondents (55.6%), while 66% were multigravida with the space between pregnancy of 12-24 months (57.8%). The stool analysis of most respondents showed the presence of yeast (24%), although the presence of some parasites were observed as well. For the thick drop, most respondents were diagnosed with malaria (77.6%). The iron supplementation, deworming, and counseling during the antenatal sessions proved effective against iron deficiency anemia. Given the seriousness of the situation in pregnant women, it is necessary that these strategies of effectiveness must be applied for a good management of anemia.